THE CORRELATION BETWEEN ANXIETY LEVELS AND SLEEP QUALITY IN ASTHMA UFFERERS AT THE LEMAHABANG HEALTH CENTER - Suryadi, Sri Mulyani; Simamora, Rotua Suriany; Meliyana, Ernauli (Rena Cipta Mandiri, 2024)
Anxiety often occurs in society and has become a part of everyday life. Individuals who experience anxiety can disrupt the homeostatic system and their individual functions, so they need to adjust well in order to be overcome. The worse the level of improvement in the quality of sleep. Sleep disturbances can lead to a deterioration in quality of life. Such sleep disturbances can result in daytime fatigue and can affect functional status and quality of life. Mental disorders associated with sleep disorders are anxiety. Asthma and asthma attacks are two different things, usually people with severe persistent asthma can experience mild asthma attacks but sometimes people with asthma who are classified as episodic rarely can experience asthma attacks even if not treated quickly resulting in loss of breath and can cause death. Research Purpose : This study aims to determine the relationship between anxiety and sleep quality in asthma sufferers at the Lemahabang Public Health Center. Research Method : The research method used is quantitative research with research design using analytical observational research design with cross sectional. The population of this study were all asthma sufferers at the Lemahabang Health Center totaling 52 people. Research Result: From the results of data analysis, it was found that the p-value was 0.000 which means <0.05 that there was a correlation between anxiety levels and sleep quality in asthma r ufferers at the Lemahabang Health Center. Conclusion : There was a correlation between anxiety levels and sleep quality in asthma sufferers at the Lemahabang Health Center. Keyword: Sleep Quality, Anxiety, Asthma Sufferers